2006
DOI: 10.1038/sj.cdd.4401909
|View full text |Cite
|
Sign up to set email alerts
|

The versatile interactions of p53 with DNA: when flexibility serves specificity

Abstract: The tumor suppressor p53 exerts versatile interactions with DNA. Of importance is the binding of wild-type p53 to p53-responsive elements in promoters of p53 target genes. This interaction is complex and determined by DNA sequence and structure, and involves the p53 core DNA binding and the C-terminal domain. In addition, wild-type p53 binds linear DNA with high affinity in a sequence-independent manner, and non-B DNA in a DNA strictly structure-selective mode that is not dependent on the presence of a p53-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Despite rapidly accumulating evidence, the knowledge of the molecular details of the transcriptional activity of mutant p53 is still very scarce; (c) recent work by Di Agostino et al Mutant p53: an oncogenic transcription factor S Strano et al mutant p53 is recruited in vivo to such regulatory regions through the physical interaction with the transcription factor NF-Y (Figure 3). Altogether, these results show that the repertoire of the genes regulated by p53 gain-offunction mutants can be dictated by the specific interaction partner; (d) original work from Deppert's lab has shown that mutant p53 tightly associates with the nuclear matrix in vivo, and with high affinity with nuclear matrix attachment region DNA in vitro Koga and Deppert, 2000;Gohler et al, 2005;Kim and Deppert, 2006). These findings suggest that mutant p53 interacting with key structural components of the nucleus exerts its gain-of-function activity through the perturbation of the nuclear structure and function.…”
Section: Introductionmentioning
confidence: 87%
“…Despite rapidly accumulating evidence, the knowledge of the molecular details of the transcriptional activity of mutant p53 is still very scarce; (c) recent work by Di Agostino et al Mutant p53: an oncogenic transcription factor S Strano et al mutant p53 is recruited in vivo to such regulatory regions through the physical interaction with the transcription factor NF-Y (Figure 3). Altogether, these results show that the repertoire of the genes regulated by p53 gain-offunction mutants can be dictated by the specific interaction partner; (d) original work from Deppert's lab has shown that mutant p53 tightly associates with the nuclear matrix in vivo, and with high affinity with nuclear matrix attachment region DNA in vitro Koga and Deppert, 2000;Gohler et al, 2005;Kim and Deppert, 2006). These findings suggest that mutant p53 interacting with key structural components of the nucleus exerts its gain-of-function activity through the perturbation of the nuclear structure and function.…”
Section: Introductionmentioning
confidence: 87%
“…We also considered the possibility that p53 binds directly in a sequence independent manner to repetitive or low complexity sequences that might serve as a structural binding motif. 11 However, this is unlikely because only 6.9% of the peaks with no motif were in repeats (UCSC repeat masker) compared with 28% of the 743 peaks found in repeats.…”
Section: Methodsmentioning
confidence: 99%
“…10 It also can bind to simple repeats and a variety of DNA structures and mismatches, although these have not been shown to affect transcription. 11,12 Binding of p53 to DNA is highly cooperative, 13 which has been proposed to be particularly important at imperfect binding sites. 14 Despite the fact that 20% of the putative p53 binding sites contain one or more CpG dinucleotides, and p53 binding was proposed to be affected by their methylation state, 15 the impact of DNA methylation on p53 genome-wide binding has not been investigated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…However, additional complexity is provided by evidence that modulation of p53 itself may also allow the differential recognition of target-gene promoters. One interesting possibility is that changes in the conformation of p53 allow selective recognition of different p53-binding sites, a suggestion that is supported by the high degree of flexibility seen in the ability of p53 to bind DNA (Kim and Deppert, 2006). This model might mean that the mutants of p53 that only activate expression of one group of genes are locked in the conformation that only recognises the binding sites present in these promoters.…”
Section: Differential Activation Of Target Genesmentioning
confidence: 99%